Unveiling optical in-plane anisotropy of 2D materials from oblique incidence of light. (30th May 2019) - Oliva-Leyva, M; de la Cruz, G Gonzalez
Abstract: In this work, we present a theoretical study of the dispersion of linearly polarized light between two dielectric media separated by an anisotropic two-dimensional (2D) material under oblique incidence. Assuming that the 2D material is a conducting sheet of negligible thickness, generalized Fresnel coefficients are derived as a function of usual quantities (e.g. refraction indexes and scattering angles) and the anisotropic in-plane optical conductivity of the interstitial 2D material. In particular, we analyzed the modifications due to the 2D material of two classical optical phenomena: the Brewster effect and the total internal reflection. As a application, our general findings are particularized for uniaxially strained graphene. Effects of a uniaxial strain on the Brewster angle and the reflectance (under total internal reflection) are evaluated as a function of the magnitude and direction of strain.